CSF IgA NMDAR antibodies are potential biomarkers for teratomas in anti-NMDAR encephalitis. Issue 6 (December 2015) - Desestret, Virginie; Chefdeville, Aude; Viaccoz, Aurélien; Bost, Chloe; Ducray, François; Picard, Géraldine; Rogemond, Veronique; Chaffois, Marie-Oceane; Blanc, Charlotte; Bardel, Claire; Treilleux, Isabelle; Pascual, Olivier; et al.
Abstract : Objective: To evaluate the presence of immunoglobulin A (IgA) subtype of anti-NMDA receptor (NMDAR) antibodies (IgA-NMDAR-Abs) in the CSF of patients with immunoglobulin G (IgG)-NMDAR-Ab encephalitis and to describe the potential association with a specific clinical pattern. Methods: The retrospective analysis for the presence of IgA-NMDAR-Abs in 94 CSF samples from patients with anti-NMDAR encephalitis diagnosed between October 2007 and February 2014 was conducted at the French Reference Centre on Paraneoplastic Neurological Syndrome. This observational study compared 39 patients with both IgA- and IgG-NMDAR-Abs to 55 patients with only IgG-NMDAR-Abs. Results: In the retrospective cohort, 41% of the patients with NMDAR-Ab encephalitis had both CSF IgG- and IgA-NMDAR-Abs. Approximately half of the IgA-NMDAR-Ab-positive patients (18/38, 49%) definitively possessed associated tumors, primarily ovarian teratomas (17/18, 94%), compared with only 5% (3/55) of the patients in the IgA-NMDAR-Ab-negative group ( p < 0.001). In the adult female population at risk for ovarian teratoma, the detection of CSF IgA-NMDAR-Ab positivity showed 85% sensitivity, 70% specificity, a 57% positive predictive value, and a 90% negative predictive value for the diagnosis of ovarian teratoma. No other specific clinical features or clinical outcome were associated with CSF IgA-NMDAR-Ab positivity. Conclusion: These results suggest that in patients with IgG-NMDAR-Ab encephalitis, CSF IgA-NMDAR-Abs could be used as a biological marker for the presence of an ovarian teratoma.